Classification of Bulgarian Advertising Styles – Findings of Advertising Content Analysis in Bulgarian Media - Katrandjhiev, Hristo (UNWE Yearbook, 2009)
The objective of the study presented in this paper is to classify the executional styles in Bulgarian advertising. For the completion of this task the author applies the research method of content analysis of advertisements in Bulgarian media. Creating a typology of executional styles in modern advertising means to identify and classify the typical or most often used executional styles. At the same time the author analyzes the connection between the advertising appeals from one hand and the executional styles from the other. The major advertising appeals are described and analyzed from the point of view of their practical application in advertising practice.The results of the study confirm the existence of 7 major executional styles in Bulgarian advertising practice. These executional styles include: (1) style of advertising presentation; (2) style of advertising associations; (3) "educational" style; (4) dramatic style; (5) entertaining style; (6) "fantastic" style; (7) style of urging consumer to action. The detailed analysis however revealed numerous "sub"-styles within each major executional style. All of them are described and illustrated in the paper.